The position’s of libraries on social media - Dessy Harisanty; Rahma Sugihartati; Koko Srimulyo; Norizan Anwar (Cogent Social Sciences, 2024)
Libraries as public spaces cannot be separated from the subjective assessments of the public as users which are represented in the form of discourse on social media. This research aims to dismantle this discourse. The method used is qualitative. Data collection is carried out by crawling data on social media via the Brand24 application. Based on the data collection process from Twitter, blogs, news, and the web 18,461 texts were obtained in the form of discourses about libraries in the scope of Indonesia. From these, 82 texts were selected to represent the discourse used in the analysis. Data were categorized and analyzed using a critical discourse analysis perspective coined by Teun A. van Dijk, based on text, social cognition, and social context. The results of this research show that the discourses shared on social media, both positive and negative, are not absolute truth and are still worthy of discussion according to the interpretation of each individual who views them.